The human capital–economic growth nexus in SSA countries: what can strengthen the relationship?. Issue 9 (29th July 2020) - Karambakuwa, Roseline Tapuwa; Ncwadi, Ronney; Phiri, Andrew
Abstract : Purpose: The purpose of this study is to examine the impact of human capital on economic growth for a selected sample of nine SSA countries between 1980 and 2014 using a panel econometric approach. Design/methodology/approach: The authors estimate a log-linearized endogenous using the fully modified ordinary least squares (FMOLS) and the dynamic ordinary least squares (POLS) applied to our panel data time series. Findings: The empirical analysis shows an insignificant effect of human capital on economic growth for our selected sample. These findings remain unchanged even after adding interactive terms to human capital, which are representatives of government spending as well as foreign direct investment. Nevertheless, the authors establish a positive and significant effect of the interactive term between urbanization and human capital on economic growth. Practical implications: The results emphasize the need for African policymakers to develop urbanized, "smart", technologically driven cities within the SSA region as a platform toward strengthening the impact of human capital-economic growth relationship. Originality/value: This study becomes the first in the literature to validate the human capital–urbanization–growth relationship for African countries.